On impersonals in Kashubian, Polish, and Silesian: Generic modals and [3SG] in null subject languages. - Ruda, Marta (Journal of Slavic Linguistics)
In this paper I offer data showing that Kashubian, Polish, and Silesian have a largely parallel system of impersonals with a syntactically projected subject. In the structures with agreeing verbal morphology such as (most) modal impersonals in Kashubian, the subject is nominative, implying that in these structures [Case] is present in its projection. In the structures with default verbal morphology such as modal impersonals in Polish and Silesian, the subject is not nominative, which follows from the lack of verbal [φ] in the clausal spine (and [Case] in the projection of the subject). The discussion has implications for developing defining characterisations of null subject languages.